PyScratch: An ease of use tool for analysis of scratch assays. (September 2020) - Garcia-Fossa, Fernanda; Gaal, Vladimir; de Jesus, Marcelo Bispo
Highlights: ● PyScratch is an open source tool that autonomously performs quantitative analysis of in vitro scratch assays. ● PyScratch automates analysis and likely minimizes human error. ● PyScratch offers a user-friendly interface being useful for researchers with no programming skills. Abstract: Background and objective: Image acquisition has greatly benefited from the automation of microscopes and has been followed by an increasing amount and complexity of data acquired. Here, we present the PyScratch, a new tool for processing spatial and temporal information from scratch assays. PyScratch is an open-source software implemented in Python that analyses the migration area in an automated fashion. Methods: The software was developed in Python. Wound healing assays were used to validate its performance. The images were acquired using Cytation 5™ during 60 h. Data were analyzed using One-Way ANOVA. Results: PyScratch performed a robust analysis of confluent cells, showing that high plating density affects cell migration. Additionally, PyScratch was approximately six times faster than a semi-automated analysis. Conclusions: PyScratch offers a user-friendly interface allowing researches with little or no programming skills to perform quantitative analysis of in vitro scratch assays.